2020
DOI: 10.1016/j.econlet.2020.109074
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping ownership, endogenous quality, and welfare

Abstract: This paper investigates how overlapping ownership a¤ects quality levels, consumer surplus, …rms' pro…ts and welfare when the industry is a vertically di¤erentiated duopoly and quality choice is endogenous. This issue is particularly relevant since recent empirical evidence suggests that overlapping ownership constitutes an important feature of a multitude of vertically di¤erentiated industries. We show that overlapping ownership while detrimental for welfare, may increase or decrease the quality gap, consumer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…It is being argued that cross share‐holding may yield harms to competition, however, social welfare may increase (Farrell & Shapiro, 1990). Several recent papers focusing on cross‐holding and its influences on R&D (López & Vives, 2019; Papadopoulos et al, 2019; Vives, 2020), investment portfolios (Shy & Stenbacka, 2020), product quality (Brito et al, 2020), licensing (Leonardos et al, 2021), and vertical structure (Alipranti et al, 2022; Chen et al, 2021), have enriched our understanding of cross‐holding in various aspects. Fanti and Buccella (2021) address that reciprocal cross‐ownership will solve prisoner's dilemma under appropriate degrees of product competition.…”
Section: Introductionmentioning
confidence: 99%
“…It is being argued that cross share‐holding may yield harms to competition, however, social welfare may increase (Farrell & Shapiro, 1990). Several recent papers focusing on cross‐holding and its influences on R&D (López & Vives, 2019; Papadopoulos et al, 2019; Vives, 2020), investment portfolios (Shy & Stenbacka, 2020), product quality (Brito et al, 2020), licensing (Leonardos et al, 2021), and vertical structure (Alipranti et al, 2022; Chen et al, 2021), have enriched our understanding of cross‐holding in various aspects. Fanti and Buccella (2021) address that reciprocal cross‐ownership will solve prisoner's dilemma under appropriate degrees of product competition.…”
Section: Introductionmentioning
confidence: 99%
“…It is being argued that cross share-holding may yield harms to competition, however, social welfare may increase with cross-holding considering asymmetric technologies among firms (Brito, et al, 2020;Farrell & Shapiro, 1990). Several recent papers focusing on cross-holding and its influences on R&D (López & Vives, 2019;Vives, 2020), licensing (Brito, et al, 2020), investment portfolios (Shy & Stenbacka, 2020), product quality (Leonardos, et al, 2021), vertical structure (Chen, et al, 2021), have enriched our understanding of cross-holding in various aspects. Fanti (2013Fanti ( , 2016 analyses the effects of an increase in the share of cross ownership in a differentiated Cournot duopoly with firm-specific monopolistic unions with unilateral and bilateral holding, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Vertical cross‐holding or horizontal cross‐holding have been criticized reducing the incentive of firms to compete aggressively, therefore leading to higher product prices and lower industry output (Reynolds & Snapp, 1986). It is being argued that cross share‐holding may yield harms to competition, however, social welfare may increase with cross‐holding considering asymmetric technologies among firms (Brito, et al., 2020; Farrell & Shapiro, 1990). Several recent papers focusing on cross‐holding and its influences on R&D (López & Vives, 2019; Vives, 2020), licensing (Brito, et al., 2020), investment portfolios (Shy & Stenbacka, 2020), product quality (Leonardos, et al., 2021), vertical structure (Chen, et al., 2021), have enriched our understanding of cross‐holding in various aspects.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have examined the positive welfare effect of PPO in the areas of innovation and advanced knowledge or technology transfer. Bayona and López (2018) and Brito et al (2020) examined how PPOs affect cost-reducing and quality-enhancing research and development (R&D), respectively. Lopez and Vives (2019) found that when demand is less prominent and spillovers are high or moderate, PPO can increase R&D investments and outputs.…”
Section: Introductionmentioning
confidence: 99%
“…Bayona and López (2018) and Brito et al. (2020) examined how PPOs affect cost‐reducing and quality‐enhancing research and development (R&D), respectively. Lopez and Vives (2019) found that when demand is less prominent and spillovers are high or moderate, PPO can increase R&D investments and outputs.…”
Section: Introductionmentioning
confidence: 99%